Improvement of dielectric, magnetic and thermal properties of OPEFB fibre–polycaprolactone composite by adding Ni–Zn ferrite - Ahmad, Ahmad Fahad; Abbas, Zulkifly; Obaiys, Suzan J.; Abdalhadi, Daw M. (MDPI, 2017)
The dielectric and magnetic behaviour and thermal properties of composites based on nickel–zinc ferrite (NZF) filler can be improved by the addition of various types of materials. Amongst others, ferrite–polymer composites have been subjected to a wide range of research, due to their extensive applications: electromagnetic interference shielding, microwave absorption, electrodes and sensors. Currently, the interest in scientific and technical searches for the potential outcomes of ferrite–polymer materials due to their different uses in applications such as telecommunication applications, microwave devices and electromagnetic interference shielding has been growing stronger. The dielectric and magnetic behaviour and thermal properties for such composite materials depend on size, shape and the amount of filler addition. Nickel–zinc ferrite material was prepared using the conventional solid-state reaction technique. This study highlights the development of microwave-absorbing material from NZF by adding natural fibres, Oil Palm Empty Fruit Bunch (OPEFB) and polycaprolactone (PCL). OPEFB is considered in this study because it is a solid waste product of the oil palm milling process which is widely and cheaply available. The use of OPEFB in this product may save the environment from oil palm solid waste. A Thermal Hake blending machine was used in blending the powder structure of NZF + OPEFB + PCL, which made it homogeneous. These composites were characterized by the use of Fourier transform infrared (FTIR) spectrometry and scanning electron microscopy (SEM). The thermal degradation behaviour of the composites was analyzed using thermogravimetric analysis (TGA) and differential thermogravimetric (DTG) thermograms. The effective permittivity and effective permeability was obtained over a broad frequency range from 8 to 12 GHz at room temperature. It was observed that the values of effective permittivity and permeability increased as the content of NZF content increased. A rectangular waveguide connected to a microwave vector network analyser (PNA) (HP/Agilent model PNA E8364B) was employed in measuring the reflection coefficient S11 and transmission coefficient S21 parameters of composites for different percentages of NZF filler. This parameter was then used in calculating the microwave absorbing properties (dB).